2018
DOI: 10.22463/0122820x.1680
|View full text |Cite
|
Sign up to set email alerts
|

Physical-ceramic characterization of clays used in the manufacture of mansory products for construction

Abstract: Nowadays, in Colombia, specifically in the north-eastern, in Santander region, the process of mixing the ceramic paste used to manufacture masonry products for construction (H- 10 bricks, tiles, roof tiles, etc.) is done manually. For this reason, approximately 70% of the companies do not possess the technological tools which facilitate the prediction of the behavior of the raw material (clay). The main objective of this research is to formulate mixtures at a laboratory-level in order to verify the physical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In the brickyard Las Casitas; (i) P4M5 has a medium plasticity behavior, (ii) P4M6 has low plasticity, (iii) P5M7 is considered low plasticity, and (iv) P5M8 is low plasticity. These results are similar to those reported by García-León for a clay from the Norte de Santander region in Colombia [26] and another similar study [30]. The interpretation of the results for each of the samples is observed in Table V.…”
Section: Physical Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…In the brickyard Las Casitas; (i) P4M5 has a medium plasticity behavior, (ii) P4M6 has low plasticity, (iii) P5M7 is considered low plasticity, and (iv) P5M8 is low plasticity. These results are similar to those reported by García-León for a clay from the Norte de Santander region in Colombia [26] and another similar study [30]. The interpretation of the results for each of the samples is observed in Table V.…”
Section: Physical Characterizationsupporting
confidence: 90%
“…Furthermore, it was found that in the crystalline phases of clays P5M7 and P5M8, quartz existed in a large proportion as a common mineral in both. This mineral guarantees clay the character of being a degreasing material, which is related to the granulometry where these two have a higher Table 8 shows the results of the compressive strength of solid brick units with a value lower than 15 MPa, indicating that the samples should not be for structural use, only 5 units from the El Cielo brickyard and 4 from Las Casitas reach the limit to be classified as non-structural use [30], [31]. Therefore, the samples of the selected companies must be mixed with others of better quality to optimize economic resources and achieve a product that meets the requirements of current Colombian regulations.…”
mentioning
confidence: 98%